2017
DOI: 10.1177/1558944717732065
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Plate Versus Screw Fixation for Segmental Scaphoid Fractures: A Biomechanical Study

Abstract: In scaphoid fractures with segmental defect, plate and screw fixation demonstrate similar loads to failure, but plate fixation performs superiorly to screw fixation for gap recovery after an applied load to failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Treatment of scaphoid nonunion with locking plates has been described previously. Biomechanical studies have reported that locking plate fixation has superior anti-rotational forces than fixation with a headless compression screw [ 8 ] and equal or better resistance to axial pressure loading [ 9 ]. Although there have been previous reports that plate fixation did not have superior mechanical characteristics to headless compression screws [ 10 ], plate fixation seems to be the most consistent biomechanical form of osteosynthesis with a high level of fragment stability and safe bone graft fixation maintaining the scaphoid length [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of scaphoid nonunion with locking plates has been described previously. Biomechanical studies have reported that locking plate fixation has superior anti-rotational forces than fixation with a headless compression screw [ 8 ] and equal or better resistance to axial pressure loading [ 9 ]. Although there have been previous reports that plate fixation did not have superior mechanical characteristics to headless compression screws [ 10 ], plate fixation seems to be the most consistent biomechanical form of osteosynthesis with a high level of fragment stability and safe bone graft fixation maintaining the scaphoid length [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed bone grafting from the distal radius because of a previous report that bone grafting from the distal radius and from the iliac bone had similar fusion rates in the treatment of scaphoid nonunion [ 11 ], and because the procedure could be performed under brachial plexus blocks. Furthermore, to perform firm fixation while maintaining the scaphoid length, fixation with a locking plate was performed [ 9 ]. In addition, the scaphoid was indirectly fixed and rested by temporarily fixing the midcarpal joint.…”
Section: Discussionmentioning
confidence: 99%
“…The scaphoid plate is preferably used in the treatment of dislocation or comminuted fracture and nonunion [ 9 ]. A biomechanical study of plate versus screw in segmental scaphoid fracture showed that plate and screw fixation demonstrate similar loads to failure, but plate fixation was superior for gap recovery after an applied load to failure [ 13 ]. Another benefit of a plate is that it can prevent the extrusion of cortico-cancellous bone grafts in cases of nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…In the current case, after diagnosing the female with segmental scaphoid fracture, the treating team decided to use one 1 headless screw agist common surgical intervention with high success rate by returning to the normal movement range for the wrist with no pain. This was unlike to what reported by Goodwin JA., et al [13] who reported that "in scaphoid fractures with segmental defect, plate and screw fixation demonstrate similar loads to failure, but plate fixation performs superiorly to screw fixation for gap recovery after an applied load to failure". Also, Mandaleson A., et al [14] found that double screws or plate fixation demonstrated significantly greater stability, stiffness, and energy absorption when compared with a single compression screw.…”
Section: Discussionmentioning
confidence: 99%